Pengaruh Temperatur Air Terhadap Produksi Hidrogen (H2) Metode Proton Exchange Membrane (PEM) Electrolyzer - Shafiqah Yacub, Nurul; Naufal Rauf, Laode; Suryanto, Suryanto; Bhuana, Chandra (Politeknik Negeri Ujung Pandang, 2025)
Abstract: Fossil energy is still widely used in Indonesia to this day. Its continuous use causes serious environmental impacts. New energy sources, such as hydrogen, have emerged as a solution to address the ecological damage caused by fossil fuels. The unique properties of hydrogen make it an excellent fuel. This research aimed to determine the effect of water temperature on the performance of the PEM Electrolyzer and to develop a hydrogen generator design using Membrane Electrode Assembly (MEA). The research used the Proton Exchange Membrane (PEM) Electrolyzer water electrolysis method by varying the voltage, water temperature, and DC supply from a DC power supply with PWM as the current regulator. The performance of the hydrogen generator is highly influenced by the incoming water temperature. The application of Membrane Electrode Assembly (MEA) provides excellent performance in the PEM Electrolyzer. The highest performance value, 263.76%, was achieved when the current reached 7.59 A, with the water temperature at 30°C, making 30°C the optimal temperature for the PEM Electrolyzer to operate. However, when the water temperature reached its highest point at 60°C, system instability occurred, marked by a decrease in device performance to 83.28%. Furthermore, the high temperature caused swelling in the main component of the PEM Electrolyzer, the Membrane Electrode Assembly (MEA), which led to a reduction in hydrogen production.